2011
DOI: 10.1007/s10840-011-9609-6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of neutron-induced soft errors in modern cardiac pacemakers

Abstract: This experiment shows the sensibility of modern pacemakers to neutron-induced soft errors and effectiveness of backup reversion in response to irradiation. The lower neutron fluence associated with a positive test was used to propose the calculation of the very low soft error rate for the tested devices in real-life atmospheric radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Cardiac devices exposed in a controlled environment to high-density neutron beams showed a variety of responses and varied by manufacturer [4] . Single event upset risks include component thickness, battery preservation strategies, and perhaps most importantly, read and record memory functions [4] . The rate of a bit flip is a function of the device's operating voltage, semiconductor composition (wafer process), and level of exposure to radiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiac devices exposed in a controlled environment to high-density neutron beams showed a variety of responses and varied by manufacturer [4] . Single event upset risks include component thickness, battery preservation strategies, and perhaps most importantly, read and record memory functions [4] . The rate of a bit flip is a function of the device's operating voltage, semiconductor composition (wafer process), and level of exposure to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…It is also necessary to educate patients on the risk factors for terrestrial cosmic radiation and promote caution. At higher altitudes, particularly commercial air travel, there is an increased amount of cosmic radiation, making SEUs in air travel up to 20% more likely [1] , [4] . Similarly, higher latitudes may place a patient at a higher risk [1] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scattered secondary neutrons from treatment with radiotherapy cause malfunctions in cardiac implantable electronic devices (CIEDs) such as pacemakers and implantable cardioverter defibrillators [1,2]. The primary mechanism behind is that neutrons stochastically may induce single-event upsets causing the device to reset to backup mode [3,4]. The use of proton therapy for selected patients is currently increasing [5], however, the reported experience with proton therapy for patients with CIEDs is limited [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning medical application, a first clinical study reported in 1998 [5] has shown that cosmic neutron radiation could induce Single Event Upsets (SEU) in implanted devices and has evaluated its incidence in a large population of patients with Implantable Cardioverter Defibrillators, ICD [6]. Note that the SEU is the cell flip of a memory point following the crossing of an ionizing particle.…”
Section: Introductionmentioning
confidence: 99%